Intraoperative Modellierung und Registrierung für ein laparoskopisches Assistenzsystem - Röhl, Sebastian (KIT Scientific Publishing, 2013)
This book presents methods to build an intra-operative model using images of a stereo endoscope and force data. The idea is to use this model in a computer-based assistance system for laparoscopic surgery. One focus is on a method for intra-operative surface reconstruction. Furthermore, methods for intraoperative registration of pre-and intraoperative models are presented.